Digital Business Entrepreneurship Decisions: An E-Business Analysis (A Study Literature Review) - Arzo Himki; Tarisya Ramadhan; Yusuf Durachman; Erry Sigit Pramono (Pandawan Sejahtera Indonesia, 2022)
This research is a review of the literature on digital business as a subset of e-business, which has a significant impact on the fast-paced evolution of the business world today. Because of the rise of online shopping and selling, a wide range of products can now be viewed and pricing may be negotiated without having to travel to the location where the goods are sold. Detik.com, Vivanews.com, Tibunnews.com, Goals.com, Kapanlagi.com, tokobagus.com, online palasari, inexpensive online books, and various other media of various forms are a form of community search in a more ordered, efficient, and effective manner of living. The utilization of e-business in a business unit might result in profits or losses for that particular business unit. However, a closer examination reveals that the beneficial effects outnumber the negative effects. The poll results show that firms who use internet devices as a promotional medium have better sales growth than enterprises that employ traditional formats. Thousands of suppliers and millions of buyers are always available on the digital business market, allowing them to purchase goods that meet their needs. This situation demonstrates that digital business has evolved into a business that has a significant impact on entrepreneurship, resulting in a model and format that is significantly more flexible and accessible to all sectors of consumers, regardless of location.